Analisis Sifat Mekanik dan Sifat Fisik Paduan Aluminium pada Perlakuan Penuaan Buatan - Dewi Izzatus Tsamroh; Muhammad Ilman Nur Sasongko; Cepi Yazirin (TRANSMISI, 2022)
The most widely used aluminum alloy in industry is Al2024 alloy. Aluminum alloys used for automotive components are required to have good strength. The purpose of this study was to analyze the distribution of precipitates, morphology and hardness of Al2024 alloy due to artificial aging in stages I, II, and III. The test results showed that the highest distribution of precipitates (CuAl2) was in Al2024 with the third-stage artificial aging variation, and the least distribution was in the I-stage artificial aging variation. The results of morphological observations on Al2024 due to multilevel artificial aging treatment using SEM, the microstructure of Al2024 was relatively the same. (homogeneous) at each level variation. The stratified artificial aging treatment on Al2024 causes the particle size at each level variation to be smaller with closer distances. Meanwhile, the hardness value of Al2024 increased. The highest hardness of Al2024 is in the specimen with the third stage of artificial aging treatment, which is 79.66 HRE, the lowest hardness is the first stage of artificial aging, which is 74.33 HRE.